2010
DOI: 10.1007/s00018-010-0276-z
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous arterial dissection: phenotype and molecular pathogenesis

Abstract: Arterial dissection (AD) is defined as the longitudinal splitting up of the arterial wall caused by intramural bleeding. It can occur as a spontaneous event in all large and medium sized arteries. The histological hallmark of AD is medial degeneration. Histological investigations, gene expression profiling and proteome studies of affected arteries reveal disturbances in many different biological processes including inflammation, proteolytic activity, cell proliferation, apoptosis and smooth muscle cell (SMC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 151 publications
1
36
0
3
Order By: Relevance
“…Mutations were identified in a variety of genes (COL3A1, COL1A1, COL5A2, TGFBR2, TGFBR1, ACTA2) in a minority of the patients, whereas the search for mutation remained without positive results in the majority of analyzed CeAD-patients. 24 Mutations in FBN1, COL3A1, MYH11, ACTA2, TGFBR1 and TGFBR2 were found in patients with aortic dissection, particularly in familial cases, but no mutations were detected in the majority of sporadic patients. 24 A recent study identified various rare CNVs in patients with aortic dissections, disrupting different genetic processes, in particular affecting vascular smooth muscle adhesion and contractility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations were identified in a variety of genes (COL3A1, COL1A1, COL5A2, TGFBR2, TGFBR1, ACTA2) in a minority of the patients, whereas the search for mutation remained without positive results in the majority of analyzed CeAD-patients. 24 Mutations in FBN1, COL3A1, MYH11, ACTA2, TGFBR1 and TGFBR2 were found in patients with aortic dissection, particularly in familial cases, but no mutations were detected in the majority of sporadic patients. 24 A recent study identified various rare CNVs in patients with aortic dissections, disrupting different genetic processes, in particular affecting vascular smooth muscle adhesion and contractility.…”
Section: Discussionmentioning
confidence: 99%
“…24 Mutations in FBN1, COL3A1, MYH11, ACTA2, TGFBR1 and TGFBR2 were found in patients with aortic dissection, particularly in familial cases, but no mutations were detected in the majority of sporadic patients. 24 A recent study identified various rare CNVs in patients with aortic dissections, disrupting different genetic processes, in particular affecting vascular smooth muscle adhesion and contractility. 9 A large deletion encompassing the COL3A1/COL5A2 locus was identified in another patient with aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…[11]). Of course, although carotid arteries dissect [49], it is the thoracic aorta that is most vulnerable [50]. Hence, although the present results should hold qualitatively for any elastic artery, our use of data from the mouse carotid was dictated primarily by the availability of relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with this phenotypic change, a variety of SMC differentiation-specific genes, including SM myosin heavy chain (SM-MHC), calponin, SM22␣, SM ␣-actin, and smoothelin, are reduced (4,5). SMC phenotypic switching is believed to play a key role in many cardiovascular diseases, such as hypertension, atherosclerosis, coronary heart diseases, postangioplasty restenosis, and transplantation arteriopathy (4,6,7).…”
mentioning
confidence: 99%